FEM Simulation of the Cross-Wedge Rolling Process for a Stepped Shaft - Pater, Z.; Tomczak, J.; Bulzak, T. (Проблемы прочности, 2017)
The paper presents the results of numerical modeling of a cross-wedge rolling process for producing a stepped shaft. The modeling was performed with commercial software Forge NxT 1.1 using the finite element method. The numerical analysis enabled the determination of changes in the shape of the workpiece, effective strain, damage function and temperature distributions, as well as variations in the forces and torque acting on the tool. The numerical results demonstrate that personal computers can today be used to model even the most difficult cases of the cross-wedge rolling process, in which complex shapes of the tools and thermal phenomena occurring during the forming process have to be taken into consideration Представлены результаты численного моделирования процесса поперечно-клиновой прокатки для изготовления ступенчатого вала. Моделирование выполнялось на базе коммерческой программы Forge NxT 1.1 с использованием метода конечных элементов. Численное решение позволило определить изменения формы изделия, эффективной деформации, функции повреждаемости и распределения температур, а также сил и крутящих моментов, действующих на вал. Показано, что для моделирования даже наиболее трудных случаев процесса ПКП, когда необходимо учитывать сложные конфигурации изделий и тепловые явления, возникающие в процессе формоизменения, могут использоваться персональные компьютеры.